Patient Views on Quality of Life and Hospital Care: Results From a Qualitative Study Among Vietnamese Patients With Diabetes - Tri, Mai Trong; Khue, Nguyen Thy; Khoa, Vo Tuan; Goto, Aya (Frontiers in Communication, 2022)
Objectives: This study aimed to fill the gap between Vietnamese diabetic patients’ needs and care through a qualitative study asking about their experiences with diabetes and quality of care. Methods: Interviews with five diabetic patients were conducted at a tertiary general hospital located in southern Vietnam. The transcribed data were first subjected to quantitative text analysis using KH coder to identify major categories of frequently used words, followed by a qualitative analysis of selected cases using the Steps Coding and Theorization (SCAT) method. Results: The major categories of frequently used words were chronic health conditions, services, facilities, insurance, patient–doctor communication, and medication. SCAT analysis of three selected cases identified six themes: “Disregarding the disease at the early stage”, “Fear of complications”, “Satisfaction with hospital services and medical staff”, “Insurance-related problems”, “Long waiting times”, and “Communication barriers between patients and doctors”. Patients were satisfied with improved hospital facilities and services; however, the overloading of one hospital led to long waiting times and communication difficulties with doctors. Difficulties with health insurance were also observed, and patients were rather passive in disease management and needed to be empowered through improved communication with doctors and other care providers. Conclusion: These findings from our trial of introducing a qualitative study into service evaluation suggest that listening to patients can help health providers learn their perspectives and be more responsive to their needs.